Konsep Pendidikan Persfektif Syaikh Al-Zarnuji: Analisis Kitab Ta’limul Muta’allim - Saman, Kiagus Akbar; Sukandar, Ahmad; Fathurrohman, Asep Ahmad (Edukasi: Journal of Educational Research, 2021)
This paper discusses the concept of education according to Shaykh Al-Zarnuji which is written in the book of ta'limul muta'allim. This research is categorized as library research, using qualitative methods. The data collection techniques in this study use documentation techniques, and in data analysis the authors use content analysis techniques. This study found that there are at least five characteristics of education as outlined by Shaykh Al-Zarnuji in his book ta'limul muta'aalim. The five characters are as follows; First, the obligation to seek knowledge for every human being. Second, have good intentions; Every student of knowledge must have good intentions, namely to finish ignorance and get the pleasure of Allah SWT. Third, respect the teacher, because without the teacher it is impossible for the learning process to take place. Fourth, seriousness in learning. Fifth, apply the morals that begin in life as a reflection of a student of knowledge. In addition, the author also finds that the concept of education proposed by Shaykh Al-Zarnuji is closely related in realizing the goal of the independent-learning program, namely the creation of superior human resources.